KRAS G12C inhibitor combination therapies: current evidence and challenge - Miyashita, Hirotaka; Kato, Shumei; Hong, David S. (Frontiers in Oncology, 2024)
Although KRAS G12C inhibitors have proven that KRAS is a "druggable" target of cancer, KRAS G12C inhibitor monotherapies have demonstrated limited clinical efficacy due to primary and acquired resistance mechanisms. Multiple combinations of KRAS G12C inhibitors with other targeted therapies, such as RTK, SHP2, and MEK inhibitors, have been investigated in clinical trials to overcome the resistance. They have demonstrated promising efficacy, especially by combining KRAS G12C and EGFR inhibitors for KRAS G12C mutated colorectal cancer. Many clinical trials of combinations of KRAS G12C inhibitors with other targeted therapies such as SOS1, ERK, CDK4/6, and wild-type RAS are ongoing. Furthermore, preclinical data have suggested additional promising KRAS G12C combinations with YAP/TAZ-TEAD inhibitors, FAK inhibitors, and farnesyltransferase inhibitors. The combinations of KRAS G12C inhibitors with immunotherapies and chemotherapies have also been conducted, and the preliminary results were reported. More recently, KRAS-targeted therapies not limited to KRAS G12C are being developed, potentially broadening the treatment landscape of KRAS-mutated cancers. Rationally combining KRAS inhibitors with other therapeutics is likely to play a significant role in future treatment for KRAS mutated solid tumors.